PENILAIAN ORGANOLEPTIK, KANDUNGAN PROKSIMAT, BESI (Fe), KOLESTEROL, DAN CEMARAN LOGAM PLUMBUM (Pb) NUGGET KERANG KALANDUE (Polymesoda erosa) - B, Sukina; Astati, Astati; Ahmad, Ahmad; Imanuddin, Imanuddin (Jurnal Sains dan Teknologi Pangan, 2021)
ABSTRACT The purpose of this study was to determine the organoleptic assessment of kalandue scallop nuggets with carrot substitution, then continued with the determination of iron content, cholesterol, food quality and food safety of kalandue mussel nuggets selected formula based on test parameters, proximate content, and lead contamination. This study used a completely randomized design (CRD) with four formulas, namely P1 (ratio of kalandue scallops and carrots 100:0), P2 (ratio of kalandue scallops and carrots 75:25), P3 (ratio of kalandue scallops and carrots 50:50), and P4 (ratio of kalandue mussels and carrots 25:75). Organoleptic assessment data were analyzed using non-parametric statistics with the Kruskal Wallis Hedonic test. The results show that the average score for the organoleptic assessment of kalandue scallop nuggets from all test parameters of the P2 formula was preferable to other formulas. Carrot substitution in making kalandue shellfish nuggets had no effect on the organoleptic assessment of all test variables. The results show that the moisture, carbohydrates, protein, fat, ash, crude fiber, Fe, and cholesterol contents were 49.38%, 31.41%, 13.25%, 4.89%, 0.96%, 0.09%, 12.59 mg/100g, and 2.78 mg/100g, respectively. In addition, no lead contamination was found. The conclusions of this research are: the P2 Formula was the best kalandue scallop nugget formula. It met the quality requirements of fish nuggets according to SNI 7758:2013 based on test parameters, proximate content, and lead contamination.  Keywords: kalandue scallop nuggets, organoleptic attributes, proximate, cholesterol, iron, lead contamination ABSTRAKTujuan penelitian ini untuk mengetahui penilaian organoleptik nugget kerang kalandue dengan substitusi wortel, kemudian dilanjutkan dengan penentuan kandungan besi, kolesterol, serta mutu dan keamanan nugget kerang kalandue formula terpilih berdasarkan parameter uji: kandungan proksimat, dan cemaran logam Plumbum. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan Empat formula, yaitu: P1 (perbandingan kerang kalandue dan wortel 100:0), P2 (perbandingan kerang kalandue dan wortel 75:25), P3 (perbandingan kerang kalandue dan wortel 50: 50), dan P4 (perbandingan kerang kalandue dan wortel 25: 75). Data penilaian organoleptik dianalisis dengan menggunakan statistik non-parametrik dengan uji Hedonik Kruskal Wallis. Hasil penelitian menunjukkan rerata skor penilaian organoleptik nugget kerang kalandue dari semua parameter pengujian formula P2 lebih disukai dibanding formula lainnya. Substitusi wortel pada pembuatan nugget kerang kalandue tidak berpengaruh pada penilaian organoleptik semua variabel pengujian. Hasil pemeriksaan kandungan air, karbohidrat, protein, lemak, kadar abu, serat kasar, Fe, dan kolesterol masing-masing adalah 49,38%, 31,41%, 13,25%, 4,89%, 0,96%, 0,09%, 12,59 mg/100g, dan 2,78 mg/100g, serta tidak ditemukan cemaran logam Pb. Kesimpulan hasil penelitian ini adalah: Formula P2 merupakan formula nugget kerang kalandue terbaik, serta telah memenuhi persyaratan mutu nugget ikan menurut SNI 7758:2013, berdasarkan parameter uji: kandungan proksimat, dan cemaran logam Plumbum.Kata kunci: nugget kerang kalandue, penilaian organoleptik, kandungan proksimat, kolesterol, zat besi, cemaran logam Plumbum